STRATEGI MAXIM MENGEMBANGKAN TRANSPORTASI UNTUK MEMBERIKAN PELAYANAN DAN KENYAMANAN DI BANDAR LAMPUNG - Yolanda, Indah Noversi; Bakti, Dadang Karya; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine Maxim's strategy in developing public transportation to provide user services and convenience. The theory used is the theory of customer satisfaction according to Parasuraman which contains 5 service dimension indicators including Reliability, Responsiveness, Assurance, Empathy, and Tangibles. The method in this research is to use qualitative research methods with descriptive analysis techniques and data collection techniques by interviews. The results of the study show that the maxim strategy is to offer online-based transportation services that are cheaper than its competitors, as well as a reservation feature, and a distinctive feature, namely the color yellow as branding and promotion with jackets, helmet stickers and banners, providing guarantees of legal protection for drivers, guarantee time and costs for customers, provide services in a non-discriminatory manner to all customers, and provide rules that must be obeyed and carried out by drivers. The researcher's suggestion is for Maxim City of Bandar Lampung to provide training facilities for drivers, improve the application system used, add payment features via e-wallet, and follow up strictly on drivers who commit violations in providing services to customers.